Utveckling av Mellanskogs medlemsapp - Telby, Robert (2018)
This degree project is made on behalf of Mellanskog forest owners association, to find out how Mellanskog can develop their members application. The reason for finding out what the member’s think of the application is to learn which parts of the application that they use and what parts that can be developed into something more useful for the members.